Edukasi Masyarakat Terkait Batas Wilayah melalui Sosialisasi Tertib Administrasi Batas Wilayah di Lingkungan Rukun Warga Kelurahan Sungai Jawi Kota Pontianak - Arisdiyoto, Iving; Aviani, Nawang; Handayani, Dwi Nur; Afhiani, Syarifah Nurma; Apriyani, Eka (Penerbit Goodwood, 2024)
Purpose: The delimitation of territory is an important issue during the era of regional autonomy implementation in Indonesia. Territorial boundaries must be established in order to explore the potential of each region. Therefore, territorial boundary affirmation is important for preventing territorial conflicts that can cause both material and non-material losses. One way to minimize territorial boundary conflicts is to create a map of regional boundaries based on applicable laws and regulations (administrative order). Mapping administrative boundaries to the RT/RW level can improve the quality of governance and as a form of village/village development. This educational activity was conducted to increase public awareness of the orderly administration of regional boundaries, especially in the Rukun Masyarakat area. The service activity involves three stages: preparation, implementation, and evaluation. Methodology/approach: This service activity is in the form of socialization, in which the service team collaborates with Sungai Jawi Village in Pontianak City. As a result, community members in Sungai Jawi Village became more aware of the division of administrative areas in their neighborhoods. Results/findings: This socialization provides a clearer understanding of the duties and functions of Rukun Masyarakats as well as the administrative boundaries of each RW, thereby minimizing the potential for conflict and misunderstanding regarding regional boundaries. Limitation: Focuses on maximizing the role of the community in the orderly administration of the Rukun Warga area boundaries Contribution: It is hoped that education through socialization, awareness, and active participation of the community in maintaining the administrative order of regional boundaries will increase.